2015
DOI: 10.1371/journal.pone.0135196
|View full text |Cite
|
Sign up to set email alerts
|

MADS-box Transcription Factor OsMADS25 Regulates Root Development through Affection of Nitrate Accumulation in Rice

Abstract: MADS-box transcription factors are vital regulators participating in plant growth and development process and the functions of most of them are still unknown. ANR1 was reported to play a key role in controlling lateral root development through nitrate signal in Arabidopsis. OsMADS25 is one of five ANR1-like genes in Oryza Sativa and belongs to the ANR1 clade. Here we have investigated the role of OsMADS25 in the plant’s responses to external nitrate in Oryza Sativa. Our results showed that OsMADS25 protein was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 53 publications
6
62
0
Order By: Relevance
“…It has been reported that OsMADS25 regulates PR elongation and LR formation under NO 3 − ‐rich conditions, but there were no significant differences found between the wild type and transgenic lines on NO 3 − ‐free medium (Yu et al ., ). Furthermore, we examined the expression of OsMADS25 in response to different NO 3 − conditions.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been reported that OsMADS25 regulates PR elongation and LR formation under NO 3 − ‐rich conditions, but there were no significant differences found between the wild type and transgenic lines on NO 3 − ‐free medium (Yu et al ., ). Furthermore, we examined the expression of OsMADS25 in response to different NO 3 − conditions.…”
Section: Resultsmentioning
confidence: 97%
“…More interestingly, NO 3 − accumulation in the root is positively related to exogenous auxin application (Figure S11b). Generally, our results supported the notion that NO 3 − acts as a signal to stimulate OsMADS25 to control root system development, which is consistent with a previous report (Yu et al ., ). Based on the results that OsMADS25 controlling the root development under both N‐rich and N‐free conditions (Figures ), we then proposed that, besides NO 3 − signalling pathway, OsMADS25 is also involved in other signalling(s) to regulate LR development.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently the role of OsMADS25 in the plant's responses to external nitrate was investigated. It was found that the OsMADS25 protein is found in the nucleus and cytoplasm, and works as a positive regulator to control lateral and primary root development in rice (Yu et al, 2015).…”
Section: Root Biologymentioning
confidence: 99%